Financial Development and Capital Flows: Appraisal of the "Allocation Puzzle" by the Schumpeterian Growth - Wilfried Koch; Hervé Zongo (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
We explore the role of financial development to explain the negative correlation between capital inflows and productivity catch-up. As observed in the data, countries with higher productivity growth rates export capital while countries with lower productivity growth rates receive positive capital inflows. This is contradictory to the predictions of the standard neoclassical growth model. Gourinchas and Jeanne (2013) called this paradox the "allocation puzzle". Under perfect credit market, our calibrated Schumpeterian growth model also predicts a positive correlation between capital inflows and productivity catch-up. We show that the "allocation puzzle" is more prevalent than previously thought. It can be actually generalized to a larger sample by covering more countries and a longer time period. We then introduce credit constraints in a calibrated Schumpeterian growth model to address this paradox. Our main result indicates that, when the level of financial development prevents countries from catching up relative to the world technological frontier, countries import capital to compensate for their insufficient level of domestic savings.
Keywords: 330